2002
DOI: 10.1080/07315724.2002.10719193
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Calcium Intake in Lactose Maldigesting Intolerant and Tolerant African-American Women

Abstract: In African American premenopausal women, lactose tolerance facilitates the dietary intake of calcium when compared with their lactose intolerant counterparts. Low calcium intake is associated with higher BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 38 publications
1
34
0
3
Order By: Relevance
“…The first indication of an inverse relation between calcium intake and body weight came from research by McCarron et al in 1984 (1). Since then, this inverse relation between calcium intake and body composition or body weight has been observed in a large variety of populations (2)(3)(4)(5)(6)(7)(8). In a few other studies, however, no effects were found (9)(10)(11), while, in three studies, a gender-specific effect for an altered calcium intake was observed (12)(13)(14).…”
mentioning
confidence: 77%
“…The first indication of an inverse relation between calcium intake and body weight came from research by McCarron et al in 1984 (1). Since then, this inverse relation between calcium intake and body composition or body weight has been observed in a large variety of populations (2)(3)(4)(5)(6)(7)(8). In a few other studies, however, no effects were found (9)(10)(11), while, in three studies, a gender-specific effect for an altered calcium intake was observed (12)(13)(14).…”
mentioning
confidence: 77%
“…11 Further, the significant increase in circulating These data add to a growing body of observational and clinical observations that support a role for dietary calcium and dairy foods in controlling excess adiposity. Indeed, a number of recent observational studies have noted an inverse relationship between dietary and/or dairy intake and body fat in both younger and older women, [19][20][21] AfricanAmerican women, 21 and children. [22][23][24] Evaluating the effects of intact food products, rather than supplements or pharmacological compounds, presents a unique set of problems in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies demonstrate that higher intakes of calcium or dairy products, the predominant dietary source of calcium in the US, are associated with weight loss, with some showing specificity to fat mass loss. [9][10][11][12][13][14][15][16][17][18][19][20][21] For example, we conducted a secondary analysis of data collected in our laboratory during a 2-year exercise intervention trial in 54 young, healthy women. 16 Results indicated that calcium intake, adjusted for calories, was negatively associated with changes in body weight and fat mass in women whose energy intakes were at or below the overall group mean of 1876 kcal/day.…”
Section: Introductionmentioning
confidence: 99%